2021
DOI: 10.1002/adsc.202001614
|View full text |Cite
|
Sign up to set email alerts
|

A Palladium(0)‐Catalyzed C4 Site‐Selective C−H Difluoroalkylation of Isoquinolin‐1(2H)‐Ones

Abstract: Herein, we report a Palladium(0)‐catalyzed C4 site‐selective C−H difluoroalkylation of isoquinolin‐1(2H)‐ones through a radical pathway. The present reaction enables the preparation of 2,2‐difluoro‐2‐(1‐oxo‐1,2‐dihydroisoquinolin‐4‐yl)acetates/acetamides through the direct cross‐coupling reaction of readily available isoquinolin‐1(2H)‐ones with 2‐bromo‐2,2‐difluoroacetates or 2‐bromo‐2,2‐difluoroacetamides. Therefore, this method provides an efficient and convenient approach to install a difluoroacetate or a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…More recently two examples of palladium-catalyzed processes following a similar radical pathway were reported for the para-selective difluoroalkylation of N-aryloxazolidinones [100] and the C4-selective difluoroalkylation of isoquinolinones. [101]…”
Section: Palladium Catalysismentioning
confidence: 99%
“…More recently two examples of palladium-catalyzed processes following a similar radical pathway were reported for the para-selective difluoroalkylation of N-aryloxazolidinones [100] and the C4-selective difluoroalkylation of isoquinolinones. [101]…”
Section: Palladium Catalysismentioning
confidence: 99%
“…Furthermore, the palladium-catalyzed addition of the * CF 2 CO 2 Et radical were proved to be a valuable tool for the late-stage functionalization of aromatic ketones. [151][152][153][154][155] mpg-CN was also employed by König and Antonioetti groups as a recoverable heterogeneous photocatalyst and the applicability of the method was demonstrated through multiple radical transformations, including the direct difluoromethylation of (hetero)arenes through reduction and mesolytic cleavage (I) of FGTR 29. [131] Zhang and coworkers reported that EDA complexes can serve as a versatile tool for direct aromatic functionalization.…”
Section: Ewg-substituted Difluoromethylation (Cf 2 à Ewg)mentioning
confidence: 99%
“…In the pursuit of the development of regioselective difluoromethylation protocols, palladium catalysis has also been harnessed for the addition of the ethyl difluoroacetate radical onto the para ‐position of aromatic ketones. Furthermore, the palladium‐catalyzed addition of the ⋅CF 2 CO 2 Et radical were proved to be a valuable tool for the late‐stage functionalization of aromatic ketones [151–155] . mpg‐CN was also employed by König and Antonioetti groups as a recoverable heterogeneous photocatalyst and the applicability of the method was demonstrated through multiple radical transformations, including the direct difluoromethylation of (hetero)arenes through reduction and mesolytic cleavage ( I ) of FGTR 29 [131] .…”
Section: C‐centered Radicalsmentioning
confidence: 99%
“…A procedure for synthesizing 2,2‐difluoro‐2‐(1‐oxo‐1,2‐dihydroisoquinolin‐4‐yl) acetates (or acetamides), utilizing Pd was disclosed by Zhu et al [ 66 ] Here, isoquinolin‐1( 2H )‐ones were chosen as the substrate and 2‐bromo‐2,2‐difluoroacetates (or 2‐bromo‐2,2‐difluoroacetamides) as the difluoroalkylating agent. 2.5 mol% Pd (PPh 3 ) 4 , 10 mol% Xantphos, and 2 equiv.…”
Section: Difluoroalkylation Reactionsmentioning
confidence: 99%